Impact of Climate Change on Glacier in Dhauliganga River Basin: A Geospatial Investigation - Suchitra Patayari; Payel Das; Nayan Dey (CV. Literasi Indonesia, 2022)
Glacier lake outburst is a recent incident that increases in higher glacier regions. Repeatedly Outbursts of glacier-originated lakes are prime factors for the loss of human lives as well as huge damage to local infrastructure in hilly terrain, which is recognized as hazards or natural calamities or disasters. Dhauliganga River basin is located in Uttarakhand mainly in the Chamoli district. The said research paper addresses how glacier lakes are formed and why these are busted. Data and information about the climatic condition and physical and cultural characteristics of the study area are collected from secondary sources e.g., IMD web portal, news articles, electronic media, census reports, and maps downloaded from USGS that are mapped by the QGIS software. In this research work, the area of a particular glacier zone is measured through the Google Earth software, and the measurement of the area of water bodies e.g., glacial lake with the temporal scale by Normalised Difference Water Index (NDWI), a remote sensing application. On 7th February 2021, a massive lake outburst happened in Uttarakhand, Chamoli district. Two power projects totally collapsed, many people died, and some are missing. Somehow, behind the occurrence of the glacier lake outburst (GLOF) global warming is one of the reasons for it. Anthropogenic activities influence the cause of temperature increase and climate change.